The Effect of Entrepreneurship Competency on the Sustainability of Small and Medium Enterprises (SMEs) - Nur Hidayah; Rodiah Rodiah (Budapest International Research and Critics University, 2022)
Competence is a characteristic that underlies a person to produce effective and/or superior performance in a job. SMEs, face many situations that require to make quick decisions, therefore having the ability to perform high-level conceptual activities is important for business survival and success. A competency model can explain several ways to increase the possibility of survival. The purpose of this study is to determine the determinants of entrepreneurial competencies consisting of innovation competencies, leadership competencies and network competencies, their influence on business success in small and medium enterprises (SMEs) with various types of businesses. . The study was conducted on 100 SMEs located in Tangerang City. The sampling technique used was purposive sampling. Data was collected by distributing questionnaires to respondents who were selected as research samples. The analysis technique uses SEM with Smart PLS devices. The results of the study show that innovation competence has a positive and significant impact on the survival of SMEs; leadership competence has a positive and significant influence on the survival of SMEs; network competence has a positive but not significant effect on the survival of SMEs. This research is expected to provide benefits for SMEs in using entrepreneurial competencies in order to maintain business continuity in the future. The analysis technique uses SEM with Smart PLS devices. The results of the study show that innovation competence has a positive and significant impact on the survival of SMEs; leadership competence has a positive and significant influence on the survival of SMEs; network competence has a positive but not significant effect on the survival of SMEs. This research is expected to provide benefits for SMEs in using entrepreneurial competencies in order to maintain business continuity in the future. The analysis technique uses SEM with Smart PLS devices. The results of the study show that innovation competence has a positive and significant impact on the survival of SMEs; leadership competence has a positive and significant influence on the survival of SMEs; network competence has a positive but not significant effect on the survival of SMEs. This research is expected to provide benefits for SMEs in using entrepreneurial competencies in order to maintain business continuity in the future network.